Design framework for optimizing waypoints of vehicle trajectory considering terminal velocity and impact angle constraints. Issue 8 (3rd August 2022) - Kim, Youngil; Cho, Namhoon; Park, Jongho; Kim, Youdan
Abstract : Ballistic missiles often require the terminal velocity and impact angle to be confined to a certain region around a desired value considering a wide variety of uncertain initial conditions and operational ranges. This study presents a design framework to determine optimum waypoints that satisfy constraints for given launch conditions and mission profiles. As a systematic approach to this kinodynamic motion planning problem, the proposed framework deterministically samples the waypoints. The trajectory generated by the determined waypoints in consideration of various conditions satisfies the terminal constraint. Numerical simulations are performed to demonstrate the effectiveness of the proposed method.